A framework for fully integrated building information models in a federated environment. Issue 2 (April 2016) - Solihin, Wawan; Eastman, Charles; Lee, Yong Cheol
Highlights: We discuss the importance of the use of federated models in the AECO industry. We highlight shortcomings of the current IFC schema to deal with the federated models. We propose simple yet powerful modification to the IFC schema to support this. We introduced the concept of deferred reference and object snap in. We demonstrated the potential use of the concept for federated models and versioning. Abstract: The nature of building projects necessitates building models to be designed by various parties representing disciplines in the Architecture, Engineering, Construction and Owner-operator (AECO) Industries. The federated model emerges as the most practical approach to deal with the various models, especially during design stage, construction coordination and beyond. One of the issues with the current approach is there is no real integration between the various models beyond their spatial co-location. This paper proposes a framework to enable fuller integration of otherwise disparate models into integrated models in the federated environment by enabling two critical concepts – deferred reference and an automatic object snap-in. The concepts are applied in a proposed change to an IFC schema and standardized procedure to enable the automatic snap-in mechanism. With these concepts, models could be designed and exported independently as valid, perhaps partial models and yet will remain integrated when they are inserted into the federated model. A prototype system has been developed to show the effectiveness of such integrated models.